The environment - Michael-allaby (Horus Editions Ltd Singapore, 1996)
An Inside Look is specially designed to explore the natural forces and amazing technology that shape our universe. Each volume takes readers on a remarkable adventure into an important part of our world. Striking, full-color illustrations complement a fact-filled text. Inviting two-page spreads offer many access points for readers to explore intriguing concepts. The abundance of easily understandable, cutting-edge information makes these large-format books invaluable references.